The Role of Law, Policy, and Practice in the Erosion of Economic Power in Underserved Communities - Dorothy L. White-Coleman; Sandra M. Moore (Washington University Journal of Law and Policy, 2022)
The growth of businesses owned and operated within communities is a cornerstone to economic power. This Article looks at key law, policy, and practice barriers to economic growth in underserved communities. Unfortunately, the authors' note, underserved minority communities are consistently denied the opportunity for economic growth and power due to the societal infrastructure in place. The Article explores pieces of societal infrastructure that have failed to provide the financial floor that these communities need to stand on to maximize economic power, prowess, and potential. Moore and White-Coleman use their positions as an African American lawyer investor and an African American lawyer entrepreneur to provide an illuminating vantage point on access to capital and business growth. The authors conclude that without examination through a variety of eyes and a change of the infrastructure in place, economic inequity will only persist—more laws will be generated, with more policy implications, and more communities will experience dissonance between law, policy, practice, and outcomes.
Keywords: Economic Power; Minority Communities